Entrepreneurs as Pragmatic Experimenters: A Literature Review on Causal Inference, Feedback Interpretation, and Heuristic Adaptation in Uncertain Environments - Dessy Marhandrie (International Journal of Management, Accounting & Finance (KBIJMAF), 2026)
This literature review explores how entrepreneurs act as pragmatic experimenters when navigating uncertainty, focusing on three interrelated cognitive processes: causal inference, feedback interpretation, and heuristic adaptation. Drawing on recent empirical and theoretical studies, the review synthesizes how entrepreneurs learn through iterative experimentation, adjust mental models based on ambiguous feedback, and develop heuristics to guide decision-making in unpredictable environments. The findings suggest that entrepreneurial success is often linked to adaptive learning strategies rather than predictive accuracy. This research contributes to a deeper understanding of bounded rationality and cognitive flexibility in entrepreneurial contexts, offering insights for future inquiry into how entrepreneurs balance action and learning under uncertainty.